Tick-borne encephalitis vaccination in persons with a recent history of Lyme borreliosis: Insights from a Knowledge, Attitudes and Behaviour survey in Bavaria, Germany - Stefanie Böhm; Andreas Beyerlein; Volker Fingerle; Merle M. Böhmer; Manfred Wildner (Ticks and Tick-Borne Diseases)
Tick-borne encephalitis (TBE) frequently causes severe disease or even long-term sequelae, especially in adults. In Germany, TBE risk areas are defined based on historical TBE incidences at the district level and are updated yearly. Meanwhile, almost all Bavarian districts are designated risk areas. TBE vaccination is recommended for residents or visitors of these risk areas. However, recent evidence indicates that only around one fifth of adults and one third of children and adolescents are vaccinated against TBE. Most persons notified with TBE (>97 %) are found to be not or insufficiently vaccinated. Our study aimed to identify the reasons for and against TBE vaccination among persons at high risk for tick-borne diseases (TBD) based on recent diagnosis of Lyme borreliosis (LB) to inform future preventive measures.We invited persons with a recent course of LB notified between June and August 2019 to complete a self-reported questionnaire about their knowledge, attitudes and behaviours regarding TBD-related themes. We examined self-reported TBE vaccination status using different categories based on the number of doses received.Information on their TBE vaccination status was provided by 366 of 376 eligible participants, of whom 249 (68 %) reported to have been vaccinated. Of 228 participants who provided further details, 142 (62 %) reported to have received a regular booster vaccination. Apart from age category and TBD-specific knowledge level, vaccination status was not associated with any other sociodemographic or residence-specific factors, outdoor behaviours, occupational exposure, or prior experiences with ticks or TBDs. Main reasons for vaccination were living in a TBE risk area, spending time in tick-prone environments and recommendation by a physician. Main barriers were vaccine scepticism, fear of side effects, not having given TBE vaccination any thought and low risk perception.These results suggest that in order to achieve a higher vaccination coverage to prevent TBE cases, awareness about TBE risk areas and the recommended vaccination need to be raised. Addressing misconceptions and increasing trust in vaccine safety appears crucial to address perceived barriers. Engaging trusted sources, such as medical professionals, and both implementing broad public campaigns and focusing on high-risk groups are key strategies for increasing vaccination uptake.